Study on the Application of Geneva Mechanism based on Virtual Prototype Technology - Song Yongshi; Shang Lei; He Renqi; Liu Ge (Jixie chuandong)
Taking the automatic rotating table in automatic welding process as research background,the virtual prototype of the key transmission parts geneva mechanism in workbench is established by using the three-dimensional modeling software platform,aiming at the weaknesses of traditional mechanism and combining with the motion simulation data,the design method of new geneva mechanism is put forward,and flexible body virtual prototype the new geneva mechanism is re-established. By the finite element analysis,the rationality of the design is verified. A theoretical basis for the design manufacturing and engineering application high precision automatic rotating workbench is provided.